2021
DOI: 10.1136/openhrt-2021-001647
|View full text |Cite
|
Sign up to set email alerts
|

Associations between physical activity, sedentary behaviour and left ventricular structure and function from the Echocardiographic Study of Latinos (ECHO-SOL)

Abstract: ObjectiveThe cross-sectional association between accelerometer-measured physical activity (PA), sedentary behaviour (SB) and cardiac structure and function is less well described. This study’s primary aim was to compare echocardiographic measures of cardiac structure and function with accelerometer measured PA and SB.MethodsParticipants included 1206 self-identified Hispanic/Latino men and women, age 45–74 years, from the Echocardiographic Study of Latinos. Standard echocardiographic measures included M-mode, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Previous studies in middle‐aged adults have reported conflicting relationships between increased MVPA and cardiac structure, specifically, increased LVMI. 12 , 13 , 14 There were no associations between MVPA and RWT that reflects eccentric ventricular remodeling similar to an adult study report. 12 Evidence from trained athletes suggests that eccentric hypertrophy is associated with endurance training whereas strength‐based training increases concentric hypertrophy.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Previous studies in middle‐aged adults have reported conflicting relationships between increased MVPA and cardiac structure, specifically, increased LVMI. 12 , 13 , 14 There were no associations between MVPA and RWT that reflects eccentric ventricular remodeling similar to an adult study report. 12 Evidence from trained athletes suggests that eccentric hypertrophy is associated with endurance training whereas strength‐based training increases concentric hypertrophy.…”
Section: Discussionsupporting
confidence: 77%
“…This result was also observed among normotensive participants and those with optimal fat mass and lean mass but not with high fat mass, high lean mass, or elevated BP/hypertension. Previous studies in middle‐aged adults have reported conflicting relationships between increased MVPA and cardiac structure, specifically, increased LVMI 12–14 . There were no associations between MVPA and RWT that reflects eccentric ventricular remodeling similar to an adult study report 12 .…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Five studies evaluated cardiac structure and function using echocardiography, while one assessed cardiac MRI (CMR) 27 55 83–86. Most studies suggested better myocardial function with increased PA. Thangada et al demonstrated that MVPA was associated with increased stroke volume and left ventricular (LV) end diastolic volume (EDV), and VPA was associated with larger LV mass (LVM) on CMR 83.…”
Section: Resultsmentioning
confidence: 99%